Level Up Your Learning: Gamification as an Effective Strategy to Increase Student Engagement in Algorithm Classes - Cuhanazriansyah, Muhammad Rinov; Bahmiati, Sri; Anggraini, Dina Meilina; Nur Octavian, Zacky (Universitas Putra Indonesia YPTK Padang, 2025)
Student engagement is a crucial factor for learning success, particularly in the Algorithm course, which requires abstract thinking, problem-solving, and persistence. This study aimed to compare student engagement between gamified learning and traditional methods through a quasi-experimental design involving two groups: the experimental class (n = 36) applying gamification and the control class (n = 36) receiving conventional instruction. A student engagement questionnaire covering behavioral, emotional, and cognitive dimensions was employed, supported by classroom observations and Learning Management System logs. The findings revealed that both groups had similar pre-test scores (3.12 and 3.09), but at post-test the experimental class improved significantly to 4.21, while the control class only reached 3.34. Dimension analysis showed the experimental group outperforming the control in behavioral engagement (4.35 vs. 3.41), emotional engagement (4.18 vs. 3.29), and cognitive engagement (4.09 vs. 3.32), with a large effect size (d = 0.85). Student perceptions also highlighted leaderboards (78%) and step-based missions (70%) as the most effective gamification elements, followed by achievement badges (65%). In conclusion, this study demonstrates that well-designed gamification aligned with students’ needs can serve as a more effective pedagogical strategy than traditional methods in enhancing student engagement in the Algorithm course